IMPLEMENTASI KODE ETIK PROFESI GURU SEBAGAI UPAYA PENINGKATAN PROFESIONALISME GURU DI SEKOLAH SADAR NEGERI NGANDONG - Arif, Much.Machfud; Akbar Wijaya, Abdul Latif (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2024)
Teaching is a professional task because its implementation requires certain skills through formal special education and the responsibility of the person who performs it as a competency. Teaching is inseparable from valid values. Based on the values of teachers, students, (students) and the community, the performance of educational services provided by teachers can take place based on clear instructions and decisions and based on values. Teachers think and act based on values, personal and professional ethics and illegal practices. In this context, teachers must understand the foundation of the teacher code of ethics as an ethical and moral foundation to fulfill their responsibilities. The teacher professional code of ethics is a guideline as well as a moral foundation for a teacher in professional behavior, The importance of implementing the teacher professional code of ethics in the school / madrasah environment is a way to improve organizational ethics so that individuals can behave ethically. Teachers are generally a very dominant and important factor in formal education, because they are used as role models for students and even as determinants of identity. The success of training is largely determined by the readiness of teachers in preparing students for teaching and learning activities. However, the strategic position of teachers in improving the quality of learning outcomes is strongly influenced by the professional skills of teachers and the quality of their work. All participants must abide by and abide by this professional Code of Ethics.